Mosquito as West Nile virus vector: global timeline of detection, characteristic, and biology - Natasha, Jafar Ali; Yasmin, Abd Rahaman; Kumar Sharma, Reuben Sunil; Nur-Fazila, Saulol Hamid; Nur-Mahiza, Md Isa; Arshad, Siti Suri; Mohammed, Hussni Omar; Kumar, Kiven; Keng Loong, Shih; Ahmad Khusaini, Mohd Kharip Shah (Universiti Putra Malaysia, 2023)
Mosquitoes are extremely important vectors that transmit zoonotic West Nile virus (WNV) globally, resulting in significant outbreaks in birds, humans, and mammals. The abundance of mosquito vectors combined with the migratory flying behaviour of wild birds across the globe has exacerbated the dynamics of WNV infection. Depth understanding of the WNV infection requires a comprehensive understanding of the character of the vector in terms of their taxonomy, morphology, biology, behaviours, preferences, and factors that promote their breeding. Most susceptible animals and humans may experience serious neurological illnesses such as encephalitis. Little is known about the susceptibility of mosquitoes to WNV infection. This review provides insightful knowledge about the characteristics of mosquitoes that carry WNV and their susceptibility to WNV infection. The context of mosquito’s involvement in WNV transmission is demonstrated through space and time from the 1950’s until to date. The historical timeline of WNV transmission strength was significantly intensified via the complex interactions between vector, virus, and environment. Such knowledge will provide valuable insights into vector control intervention mitigation strategies, especially in tropical climate countries like Malaysia.